Time effects of green buildings on energy use for low-income households: A longitudinal study in the United States. (July 2018) - Zhao, Dong; McCoy, Andrew P.; Agee, Philip; Mo, Yunjeong; Reichard, Georg; Paige, Freddy
Highlights: Green buildings' energy performance is stable and consistent over years. Green buildings for low-incomes use more energy in heating than cooling seasons. New residential units have significantly higher energy use than renovated units. Senior residents use 9.9% more energy in heating than non-senior residents. Financial benefits are 3.5%–9.3% of annual income of low income households. Abstract: The U.S. government has included green building policy in affordable housing programs for years. However, little to no evidence is available to elucidate this policy's efficacy in the context of energy performance and financial savings. This paper reports a longitudinal study that investigates time effects of such policy on the energy performance in low-income housing units. The researchers collected monthly energy use data over three years from 310 residential units and conducted profile analysis and MANOVA. Results indicate that (1) green buildings' energy performance is consistent across years; (2) construction type, technology level, and apartment size significantly and consistently affect energy use; and (3) occupant type inconsistently affects energy use. Results suggest financial savings of 648 per year due to reduced energy usage in green buildings. The savings equate to 9.3%, 5.6%, and 3.5% of annual income for extremely low-income, very low-income, and low-income families, respectively. Savings represent a 26.6%–37.5% reduction of energy expenditure for low-income households. Findings strongly suggest that green building incentives and the diffusion of green building practice is resulting in affordable housing systems.